Effect of micronutrients on growth and bulb production of LA hybrid lilium (Lilium longiflorum) cv. pavia - K R, NIVYA; SINGH, M K; NAMITA; JAIN, RITU; PANDEY, RAKESH; MEENA, M C (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during the 2021–22 at ICAR-Indian Agricultural Research Institute, New Delhi to determine the effect of micronutrients on the growth and bulb production of LA hybrid lilium cv. pavia. The experiment’s findings showed that applying micronutrients topically in combination was more beneficial than doing so topically alone. In contrast, a combination of ZnSO4 + MnSO4 @6 g/litre each sprayed at 40 and 60 days after planting performed better in terms of growth attributes, such as net assimilation rate (4.07 g/m2 leaf area/day), relative growth rate (9.46 mg/g/day), and specific leaf area (46.68 m2/kg). Bulb attributes included number of bulblets/plant (4.60), bulb circumference (14.97 cm), bulblets circumference (3.77 cm), weight of bulb (30.44 g), and bulblets (2.64 g) in LA hybrid lilium cv. pavia, whereas the control group showed the lowest interaction effect levels. This demonstrates that the growth of bulbous ornamental crops such as lilium benefits more from the combined administration of micronutrients. It results from the application of the ideal concentration of micronutrients at regular intervals, which increases photosynthetic rate. These micronutrients help plants accumulate biosynthates through a variety of activities and control metabolic processes that occur in plants. Additionally, they activate enzymes that enhance development and better distribute carbohydrates to various regions of the plant, such as carbonic dehydrogenase, peroxidase, tryptophan synthase, and catalase. Micronutrients are essential for all cellular and metabolic processes, and their optimal utilization enhances the quality of the crop.